﻿Updated taxonomic keys for European Hippoboscidae (Diptera), and expansion in Central Europe of the bird louse fly Ornithomyacomosa (Austen, 1930) with the first record from Slovakia - Oboňa, Jozef; Fogašová, Katarína; Fulín, Miroslav; Greš, Stanislav; Manko, Peter; Repaský, Jakub; Roháček, Jindřich; Sychra, Oldřich; Hromada, Martin (ZooKeys, 2022)
The available keys for European Hippoboscidae are outdated and do not cover all species currently known from Europe. Therefore, identification keys to the eleven genera and 31 species of the European hippoboscids are provided here. Ornithomyacomosa (Austen, 1930) (Diptera: Hippoboscidae) is recorded for the first time from the territory of Slovakia based on one female found on a sand martin, Ripariariparia (Linnaeus, 1758). The list of keds and louse flies recorded from the territory of Slovakia is increased to 20 species. New host records for Slovakia are presented.
Keywords: parasite; new host records; hippoboscid; new record; Birds; Slovakia; taxonomic keys